Hybrid receding-horizon control: Formulation and stability analysis - Parisini,T; Sacone,S (2015)
The stability analysis of an hybrid receding-horizon control scheme for non-linear discrete-time systems is addressed in the paper. The control scheme is composed of a continuous state-feedback controller and a discrete-event supervisor. Such a structure is further embedded into the structure of abstract hybrid systems. This allows to exploit the general stability theory for abstract hybrid systems to prove a novel stability result for the proposed hybrid control scheme.